2018
DOI: 10.5194/soil-2018-32
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A review on the global soil datasets for earth system modeling

Abstract: Abstract. Global soil dataset is a pillar to the challenge of earth system modeling. But it is one of the most important uncertainty sources for Earth System Models (ESMs). Soil datasets function as model parameters, initial variables and benchmark datasets for model calibration, validation and comparison. For modeling use, the dataset should be geographically continuous, scalable and with uncertainty estimates. The popular soil datasets used in ESMs are often based on limited soil profiles and coarse resoluti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In addition, the SoilGrids provides higher SOM contents than the GSDE over northern middle and high latitudes (Figures S1e and S3e), which lead to higher values of saturated soil water content and lower values of thermal conductivities of dry soils as well as volumetric heat capacities of soil solids (Figures S5b, S14a, and S14d). Dai, Shangguan, et al () evaluated several global soil composition data sets including the GSDE and SoilGrids with the soil profile database WoSIS (Batjes et al, ), and found that SoilGrids and GSDE ranked first and second in terms of the accuracy. However, this evaluation had some limitations because quite a number of WoSIS soil profiles were considered in the compilation of the GSDE and SoilGrids, indicating that the two data sets were not independently validated.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the SoilGrids provides higher SOM contents than the GSDE over northern middle and high latitudes (Figures S1e and S3e), which lead to higher values of saturated soil water content and lower values of thermal conductivities of dry soils as well as volumetric heat capacities of soil solids (Figures S5b, S14a, and S14d). Dai, Shangguan, et al () evaluated several global soil composition data sets including the GSDE and SoilGrids with the soil profile database WoSIS (Batjes et al, ), and found that SoilGrids and GSDE ranked first and second in terms of the accuracy. However, this evaluation had some limitations because quite a number of WoSIS soil profiles were considered in the compilation of the GSDE and SoilGrids, indicating that the two data sets were not independently validated.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have calibrated and validated microbial decomposition models (Robertson et al, ; Wieder et al, , ) using globally gridded soil databases such as the Harmonized Word Soils Database (HWSD, FAO/IIASA/ISRIC/ISSCAS/JRC, ) and the Northern Circumpolar Soil Carbon Database (NCSDC, Tarnocai et al, ). However, these global databases do not contain uncertainty estimates (Dai et al, ), and previous studies have identified significant differences between SOC estimates from these databases or between grid‐scale estimates from these databases and point‐scale in situ observations (Tifafi, Guenet, & Hatté, ; Figure S1). In addition, there is still no reliable globally gridded database of plant litter input.…”
Section: Introductionmentioning
confidence: 99%
“…The access to spatial explicit, consistent and reliable soil data is essential to model and map the status of soil resources globally at increasing detailed resolution in order to respond and assess world global issues (Arrouays et al, 2014;FAO, 2015;Hengl et al, 2014;Omuto et al, 2013). Furthermore, soil datasets are also one of the most important inputs for Earth System Models (ESM), to address, for example, the importance of terrestrials sinks and sources for greenhouse gases (Dai et al, 2018;Luo et al, 2016). At the same time, soils in ESM are one of the largest sources of uncertainty (Dai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, soil datasets are also one of the most important inputs for Earth System Models (ESM), to address, for example, the importance of terrestrials sinks and sources for greenhouse gases (Dai et al, 2018;Luo et al, 2016). At the same time, soils in ESM are one of the largest sources of uncertainty (Dai et al, 2018). This is why in recent years there has being a growing effort to improve access and quality of soil datasets, being one of the key goals of pillar 4 of the global soil partnership sponsored by the Food and Agriculture Organization of the United Nations (Batjes et al, 2017;Omuto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%